2021
DOI: 10.36253/techne-10617
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life management as a design tool: the case of a dry wood envelope

Abstract: This paper is part of the design strategies of reassembly and reuse of buildings according to the transition to circular economy. Specifically, the paper addresses the issue of architectural envelopes made of drywall and their executive design according to a Life Cycle Thinking (LCT) approach, based on a case study of a temporary wooden housing unit for which there are several scenarios of use and end of life once the first cycle of use of the components of the envelope has come to an end. In particular, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The key design aspects were modularity, flexibility, and adaptability of the emergency units to different sites, layouts, and conditions. The structural design was carried out in accordance with the criteria of spatial adaptability, structure modularity, and physical interchangeability, better known as DfD [28,37,38].…”
Section: Key Circular Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key design aspects were modularity, flexibility, and adaptability of the emergency units to different sites, layouts, and conditions. The structural design was carried out in accordance with the criteria of spatial adaptability, structure modularity, and physical interchangeability, better known as DfD [28,37,38].…”
Section: Key Circular Aspectsmentioning
confidence: 99%
“…A LCA assessment on the modular unit by Palumbo et al [37] showed how the extensive application of reversibility in this design resulted in 89% of the materials being reused or reusable at end-of-life without undergoing transformations. However, deterioration of the material mechanical properties and reworkings due to some irreversible connections amounted to a 4% waste production (due to nails, staples, and screws), and 7% being transformed into alternative forms and made available for other production cycles.…”
Section: Structural Detailing/design Approachmentioning
confidence: 99%
See 1 more Smart Citation